2018
DOI: 10.1038/s12276-018-0099-9
|View full text |Cite
|
Sign up to set email alerts
|

An MG53-IRS1-interaction disruptor ameliorates insulin resistance

Abstract: Mitsugumin 53 (MG53) is an E3 ligase that induces insulin receptor substrate-1 (IRS-1) ubiquitination and degradation in skeletal muscle. We previously demonstrated that the pharmaceutical disruption of the MG53-IRS-1 interaction improves insulin sensitivity by abrogating IRS-1 ubiquitination and increasing IRS-1 levels in C2C12 myotubes. Here, we developed a novel MG53-IRS-1 interaction disruptor (MID-00935) that ameliorates insulin resistance in diet-induced obese (DIO) mice. MID-00935 disrupted the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…e purpose of Park et al is to enable anyone to semiautomatically segment anatomical structures in MRI, CT, and other medical images on a personal computer. When performing semiautomatic segmentation in Adobe Photoshop, appropriate algorithms can be used, the degree of automation can be adjusted, a convenient user interface can be used, and software errors rarely occur [1]. Bailey's team aimed to compare the relationship between stride length (SL), stride frequency (SF), and speed when running on a treadmill and on the ground.…”
Section: Introductionmentioning
confidence: 99%
“…e purpose of Park et al is to enable anyone to semiautomatically segment anatomical structures in MRI, CT, and other medical images on a personal computer. When performing semiautomatic segmentation in Adobe Photoshop, appropriate algorithms can be used, the degree of automation can be adjusted, a convenient user interface can be used, and software errors rarely occur [1]. Bailey's team aimed to compare the relationship between stride length (SL), stride frequency (SF), and speed when running on a treadmill and on the ground.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the genes such as ETS1 and FGFR1 have been reported to participate in the development of PCOS ( Song et al, 2019 ; Patil et al, 2020 ). Among the other genes, KLF5 is an important transcription factor that regulates androgen-AR signaling ( Li et al, 2020 ); CYP1B1, a dioxin-inducible oxidoreductase, is involved in the metabolism of estradiol ( Muneeb et al, 2014 ); IRS1 is an insulin receptor substrate gene that mediates the control of various cellular processes by insulin ( Kasch et al, 2018 ; Park et al, 2018 ). These genes were significantly enriched in biological processes of adipocyte differentiation, insulin resistance, female pregnancy, and circadian rhythm, indicating they are likely to be involved in pathogenesis of PCOS.…”
Section: Resultsmentioning
confidence: 99%
“…For both breast cancer and AD there has been a drive for the identification of biomarkers for early detection, ultimately to improve long-term survival. Notably, pre-clinical studies have identified IRS-1, p53, PIN1 and LRP1 as individual potential therapeutic targets (126)(127)(128)(129)(130)(131)(132)(133) for both disease states, and changes in these are in themselves putative biomarkers.…”
Section: Discussionmentioning
confidence: 99%